Inicio de reflexión filosófica en estudiantes de grado sexto de la Institución Educativa Absalón Torres Camacho mediante la guía didáctica (2020)
This investigation is presented with a qualitative design approach, it searched to build with the sixth grade students of the I. E. Absalón Torres Camacho from Florida, the majority of them belonging to families of social stratum 1 and 2, the conditions of possibility for their involvement in philosophical reflections, which allowed them to analyze their environment, using the pedagogical strategy of the Didactic Guide; philosophical reflection is considered fundamental and necessary for life; philosophical reflection is an exercise that must be accessible to children, to allow them to observe and analyze life and the world in a different way; this will be possible from elements provided through a didactic guide worked up with the collected datas in the semi-structured interview to a focus group of students, and from the experiences lived with them, taking in mid the particularities and desires of them. The investigation was based on experiences of the teaching of the philosophy in children, taken from Castelló (2002), Castillo (2013), Cerletti (2000), Hoyos (2010), Lipman (1998), Nomen (2019), Pineda (2004) and Rodríguez (2015). The results showed the design of a didactic guide that motivated to students to make the philosophical exercise; the elements provided for the development of didactic guide were adjusted with the intentionality of an autonomous, democratic and critical learning which is required to encourage the philosophical spirit in sixth-grade children; and topics worked was adjusted to the characteristics of the receivers of the information, so that each of the activities generated expectation in children and it gave that the process of autonomous learning took place in each situation in which they had to produce results.